VIRULENCE OF INFECTIOUS CORYZA CAUSATIVE AGENT ISOLATES - V. A. Evgrafova; A. V. Potekhin (Ветеринария сегодня, 2018)
Virulence of 10 isolates of infectious coryza agent recovered from diseased 38-211-day-old chicken on poultry farms in the Vladimir, Moscow, Kostroma, Yaroslavl, Orenburg and Ulyanovsk Oblasts, as well as the Republic of Mordovia and Tatarstan was determined. One isolate was recovered from poultry in the Republic of Belarus. The criteria for virulence determination of Avibacterium paragallinarum were assessed according to a point system based on severity of inflammatory processes in upper respiratory airways of experimentally infected chicken. Nine out of ten isolates were found pathogenic for poultry. Chicken infected with different isolates of A. paragallinarum demonstrated the same duration of the disease stages. Diseased poultry showed similar clinical signs: rhinitis, sinusitis and conjunctivitis. In spite of the typical dynamic of the disease in infected poultry, the virulence of the isolates was different. The most virulent were isolates recovered from poultry farms in the Kostroma and Orenburg Oblasts, as well as the Republic of Tatarstan and Mordovia. The diseased chicken demonstrated abundant nasal discharge with marked swelling of the infraorbital sinus. A. paragallinarum isolates recovered in the farms of the Yaroslavl and Ulyanovsk Oblasts, as well as the Republic of Belarus showed medium virulence. The infection was characterized by moderate nasal discharges with swelling in the area of the infraorbital sinuses. Isolates recovered from the farms in the Moscow Oblast' had low virulence. Infected poultry demonstrated minor discharge from nasal passages with insignificant swelling in infraorbital sinuses. The isolate recovered in the Vladimir Oblast was found avirulent, the clinical signs were absent. Based on the suggested differentiation scheme the inhomogenuity of virulent properties of A. paragallinarum isolates was shown.